IMPLEMENTATION OF QUALITY CONTROL IN PROFESSIONAL DEVELOPMENT OF EDUCATION IN MTsN 1 PESAWARAN - Mulyana, Hapid; Patimah, Siti (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
The implementation of quality control in the professional development of teachers is a very important need. Through quality control, schools can adopt a structured and systematic approach to improving teacher professionalism. In relation to MTsN 1 Pesawaran, this study aimed to analyze quality control practices in the development of teacher professionalism in MTsN 1 Pesawaran. The research method used is a qualitative approach using interviews and observations as data collection tools. Study participants included teachers and school administrators. Collected data were analyzed using qualitative analysis techniques through data reduction, data presentation and data validation. Research results show that quality control practices play an important role in improving teacher professional development. Factors that influence faculty engagement and engagement in implementation include effective communication, planned professional and developmental development, and active participation in decision-making. With increased teacher involvement, the quality of education at MTsN 1 Pesawalan improved. The survey recommends that school leaders pay attention to the importance of establishing effective communication with teachers, organizing planned training, and involving teachers in decision-making about quality control. increase. In summary, the introduction of quality control can be an effective strategy to foster teacher professionalism and improve the quality of teaching at MTsN 1 Pesawaran.